Treatment of diabetic peripheral neuropathic pain: a systematic review of clinical trials of phase II and III - Moreira, Eliana (2019)
Diabetic Peripheral Neuropathic Pain (DPNP) is a common complication of diabetes, which affects a wide fraction of patients, and it’s likely to increase due to the prevalence of Diabetes. Diabetic neuropathy is a complication associated with patient age, illness course and hyperglycaemia severity.